2019
DOI: 10.1016/j.ijcha.2019.100362
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgical versus transcatheter aortic valve replacement: A multicenter study

Abstract: Objectives Treatment of aortic valve stenosis is evolving, indications for transcatheter approach (TAVI) have increased but also surgical valve replacement has changed with the use of minimally invasive approaches. Comparisons between TAVI and surgery have rarely been done with minimally invasive techniques (mini-SAVR) in the surgical arm. Aim of the present study is to compare mini-SAVR and TAVI in a multicenter recent cohort. Methods Evaluated were 2904 patients under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Six studies 17–22 reported the outcome of stroke. We found no significant differences between TAVR and miAVR (RR: 1.08, 95% CI: 0.40 to 2.87, n=1588, I 2 =5%) with little evidence of heterogeneity; figure 4A .…”
Section: Patient Baseline Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies 17–22 reported the outcome of stroke. We found no significant differences between TAVR and miAVR (RR: 1.08, 95% CI: 0.40 to 2.87, n=1588, I 2 =5%) with little evidence of heterogeneity; figure 4A .…”
Section: Patient Baseline Characteristicsmentioning
confidence: 99%
“…Six studies 17–20 22 23 reported on AF outcome. Initially, our results showed no significant differences between the two groups in terms of the incidence of postoperative AF (RR: 0.37, 95% CI: 0.10 to 1.32, n=1514, I 2 =89%).…”
Section: Patient Baseline Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesized that TAVR patients have decreased intra-operative complications, length of hospital stay, and develop fewer postoperative complications compared to patients who undergo SAVR and mini-SVR, as TAVR is less invasive and can obviate the need for cardiopulmonary bypass. Recently, it has been suggested that in patients who are at increased surgical risk, the decision between SAVR and TAVR should be made by the cardiology team according to individual patient characteristics [ 8 ]. We thus evaluated our patient population who had undergone one of these three surgeries with respect to their characteristics and surgical outcomes.…”
Section: Introductionmentioning
confidence: 99%